THE IMPORTANCE OF CULTURAL UNDERSTANDING IN TRANSLATION - Bakhronova Barchinoy (Journal of Higher Education and Academic Advancement, 2024)
This article talks about the importance of cultural understanding in translation and gives some important aspects of cultural communication in translation.